Hubungan Penghindaran Pajak dan Ketepatan Waktu Pelaporan Keuangan Perusahaan Industri di Indonesia - Dini Purnamasari; Heni Indah Pratiwi; Novia Hindayani (Economics and Business Faculty UNUSIA, 2026)
This study examines the relationship between tax avoidance and the timeliness of financial reporting in companies within the industrial sector. The results indicate that tax avoidance does not have a direct or significant effect on the timeliness of financial reporting. However, firm size has a significant impact on timely financial reporting. The effect of tax avoidance on reporting timeliness is not uniform across all companies; rather, it is influenced by organizational context, particularly the scale of the company. In small companies, tax avoidance practices tend to pose a significant constraint on the reporting process due to limited resources, including human resources, reporting systems, and experience in handling tax audits. This can result in delays in the preparation and submission of financial statements. Conversely, large companies have greater capacity to manage tax avoidance practices in a structured and planned manner, so these practices do not disrupt the financial reporting process.